Stabilization for a Nonlinear Beam Equation with Localized Damping - Crippa, Helvécio Rubens; Antunes, Gladson Octaviano (Cadernos do IME - Série Matemática, 2013)
In this paper, we investigate the exponential decay of the energy of a nonlinear bean equation with boundary clamped condition and a local linear dissipation of the type a(x)u_t. The method of proof is direct and is based on the multipliers technique and some integral inequalities due to Haraux and we obtain explicit decay rate.